The sketch, the tale, and the beginnings of American literature - Fash, Lydia G., 1981- (University of Virginia Press, 2020)
"Combining history, print history, and literary criticism, this book shows how short fiction of the early nineteenth century, including sketches and tales, was vital to the birth of a national literary tradition, the great American novel, and even what it meant to be American"--